Comparative efficacy of different exercise interventions in chronic non-specific low back pain: protocol of a systematic review and network meta-analysis - Heidemarie Haller; Dennis Anheyer; Holger Cramer; Gustav Dobos; Petra Klose; Anna Katharina Koch (BMJ Open)
Introduction Chronic non-specific low back pain is a major public health problem. Evidence supports the effectiveness of exercise as an intervention. Due to a paucity of direct comparisons of different exercise categories, medical guidelines were unable to make specific recommendations regarding the type of exercise working best in improving chronic low back pain. This network meta-analysis (NMA) of randomised controlled trials aims to investigate the comparative efficacy of different exercise interventions in patients with chronic non-specific low back pain.Methods and analysis MEDLINE, Scopus, Cochrane Central Register of Controlled Trials, Physiotherapy Evidence Database, SPORTDiscus, Clinicaltrials.gov and the WHO International Clinical Trials Registry Platform search portal were searched on November 2019 and without language restrictions. The search will be updated after data analysis. Studies on adults with non-specific low back pain of at least 12 weeks duration comparing exercise to either no specific intervention (ie, no treatment, wait-list or usual care at the treating physician’s discretion) and/or functionally inert interventions (ie, sham or attention control interventions) will be eligible. Pain intensity and back-specific disability are defined as primary outcomes. Secondary outcomes will include health-related physical and mental quality of life, work disability, frequency of analgesic use and adverse events. All outcomes will be analysed short-term, intermediate-term and long-term. Data will be extracted independently by two review authors. Risk of bias will be assessed using the recommendations by the Cochrane Back and Neck Group and be based on an adaptation of the Cochrane Risk of Bias tool.Ethics and dissemination This NMA will be reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses_NMA checklist. The results will be presented in peer-reviewed journals, implemented in existing national and international guidelines and will be presented to health care providers and decision makers. The planned completion date of the study is 1 July 2021.PROSPERO registration number CRD42020151472.